Teacher Support Facilitates Problem Based Learning Despite Unchanged Moral Faith Motivation: Dukungan Guru Memfasilitasi Pembelajaran Berbasis Masalah Meskipun Motivasi Akidah Akhlak Tetap - Zahra Angelita Prasetya; Abd. Madjid (Universitas Muhammadiyah Sidoarjo, 2026)
General Background In the modern globalization era, educational environments must integrate innovative pedagogies to facilitate deep and meaningful comprehension among learners. Specific Background Within moral faith instruction, conventional lecture-based delivery often fails to actively engage learners, resulting in passive participation and a highly theoretical appreciation of the subject matter. Knowledge Gap While contextual pedagogies are widely advocated, there remains a limited quantitative understanding regarding how instructional scaffolding directly translates to student drive within the specific context of moral faith subjects. Aims This study investigates the relationships between instructional scaffolding, the application of problem-oriented pedagogy, and student drive in moral faith classes at MTs Masyitoh Gamping. Results Utilizing Partial Least Squares Structural Equation Modeling on survey data from 39 respondents, the analysis revealed a strong positive relationship between instructional scaffolding and the application of problem-oriented pedagogy with an effect size of 0.803. Conversely, instructional scaffolding and problem-oriented pedagogy yielded weak associations with student drive, jointly accounting for only 6.2 percent of the variance. Novelty This research isolates the distinct boundary between instructional scaffolding for methodological application and the complex external variables governing true student drive in moral faith settings. Implications Educators must look beyond mere methodological implementation and incorporate holistic, individualized strategies involving family and psychological environments to meaningfully foster student drive. Highlights Instructional scaffolding strongly facilitated the application of problem-oriented pedagogical methods. The implemented contextual pedagogy did not directly alter the drive of the respondents. External and internal variables outside the modeled instructional framework governed respondent drive. Keywords Instructional Scaffolding; Problem Oriented Pedagogy; Moral Faith Education; Student Drive; Partial Least Squares